2023
DOI: 10.3389/fnut.2023.1045022
|View full text |Cite
|
Sign up to set email alerts
|

Clinical nutrition in surgical oncology: Young AIOM-AIRO-SICO multidisciplinary national survey on behalf of NutriOnc research group

Abstract: Malnutrition is a common condition in cancer patients which is usually associated with functional limitations, as well as increased morbidity and mortality. Based on the support of the young sections of Italian Association of Medical Oncology (AIOM), Italian Association of Radiotherapy and Clinical Oncology (AIRO) and Italian Society of Surgical Oncology (SICO) merged into the NutriOnc Research Group, we performed a multidisciplinary national survey with the aim to define the awareness of nutritional issues am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Our results call for the implementation, development, and increased use of specific tools that enable nutritional assessment to improve the management of nutritional support in clinical practice. [21]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results call for the implementation, development, and increased use of specific tools that enable nutritional assessment to improve the management of nutritional support in clinical practice. [21]…”
Section: Discussionmentioning
confidence: 99%
“…Our results call for the implementation, development, and increased use of specific tools that enable nutritional assessment to improve the management of nutritional support in clinical practice. [21] From the keyword emergent analysis, it was found that prostate cancer and lung cancer were located at the top 15. If nutritional therapy is well applied in the treatment of various types of cancer, it can change the disease and treatment process.…”
Section: Analysis Of Keyword Burstsmentioning
confidence: 99%
“…In 2020, young members of the Italian Association of Medical Oncology (AIOM), Italian Association of Radiotherapy and Clinical Oncology (AIRO), Italian Society of Surgical Oncology (SICO) and the Italian Society of Parenteral and Enteral Nutrition (SINPE) planned common research goals and founded the NutriOnc Research Group, aimed at implementing multidisciplinary strategies to improve patient quality of life 18 . The Scopus database was systematically searched between 1 January 1998 and 15 May 2023, in order to retrieve the worldwide literature concerning immunonutrition in relation to cancer, with the keywords ʻimmunonutritionʼ and ʻcancerʼ.…”
Section: Methodsmentioning
confidence: 99%
“…Accumulating evidence suggests that dietary factors, such as omega-3 fatty acids, arginine, nucleotides, and antioxidants, are thought to enhance immune cell function, modify the tumor microenvironment, reduce inflammation, and support tissue repair, thereby potentially improving cancer outcomes 15 17 . This realization has captivated the attention of the scientific community, leading to extensive investigations into the potential of immunonutrition as a complementary approach to conventional cancer therapies 12 , 18 20 . However, the evidence-based recommendations of these nutritional formulas in clinical practice are still scarce and limited to specific populations.…”
Section: Introductionmentioning
confidence: 99%